2022
DOI: 10.3389/fpubh.2021.755530
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Internet Platform in Monitoring Chinese Public Attention to the Outbreak of COVID-19

Abstract: ObjectivesThe internet data is an essential tool for reflecting public attention to hot issues. This study aimed to use the Baidu Index (BDI) and Sina Micro Index (SMI) to confirm correlation between COVID-19 case data and Chinese online data (public attention). This could verify the effect of online data on early warning of public health events, which will enable us to respond in a more timely and effective manner.MethodsSpearman correlation was used to check the consistency of BDI and SMI. Time lag cross-cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…The volume of the Baidu Information Index of each keyword was much higher than that of the Baidu Search Index and had 0 to 14 days' lag time to the number of new reported cases. This finding was inconsistent with another study that showed Sina Micro Index had advance effects on the COVID-19 outbreak 16 . This could be explained as Baidu Information Index weighted sum of and indexed the netizen's reading, comments, forwarding, likes, dislikes, and other behaviors.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The volume of the Baidu Information Index of each keyword was much higher than that of the Baidu Search Index and had 0 to 14 days' lag time to the number of new reported cases. This finding was inconsistent with another study that showed Sina Micro Index had advance effects on the COVID-19 outbreak 16 . This could be explained as Baidu Information Index weighted sum of and indexed the netizen's reading, comments, forwarding, likes, dislikes, and other behaviors.…”
Section: Discussioncontrasting
confidence: 77%
“…This finding was inconsistent with another study that showed Sina Micro Index had advance effects on the COVID-19 outbreak. 16 This could be explained as Baidu Information Index weighted sum of and indexed the netizen's reading, comments, forwarding, likes, dislikes, and other behaviors. As supply-based data, it is easily driven by hot events, which can arouse public attention and stimulate public search behavior to a certain topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, it is feasible to categorize the stages of change in public attention by keeping track of variations in the numbers of hot searches relating to the pandemic during the study period. Given the limitations of single-source hot search samples, this paper also used another common index of the public attention to certain events, the Baidu index [ 51 , 52 , 53 ], to corroborate the classification results. Jieba word classification database tools were used to process the content of the hot search entries, with “novel coronavirus”, “pandemic”, “case”, “pneumonia”, and “new pneumonia” being identified as the top five keywords.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, Baidu Index is reliable. Infodemiology studies based on the Baidu Index platform mainly involve the application in COVID-19 prediction and monitoring ( 60 , 61 ) but have not investigated OAV. In terms of research content, few studies have analyzed the spatial characteristics of OAV and their causes.…”
Section: Introductionmentioning
confidence: 99%